The Relationship of Nutritional Intake to Nutritional Status and Teenagers Learning Concentration in the Ahludz Dzikri Al-Qur’an Assembly - Alviony Berliana Aksari; Mujayanto; Riezky Faisal Nugroho; Taufiqurrahman (Journal of Nutrition Explorations, 2024)
Adolescence, which lasts from ten to twelve years, is a period of growth and development of the body that requires adequate nutritional intake to prevent problems such as malnutrition and decreased concentration in studies. According to basic data collected in October 2020, 30% of teenagers had normal nutritional status and 70% had poor nutritional status or were underweight. The purpose of this study is to ascertain how nutritional status and intake are related the focus of adolescent learning at the Ahludz Dzikri Al-Qur'an Assembly. This research uses an analytical observational method with a cross-sectional approach. Thirty students from the Ahludz Dzikri Al-Qur'an Council participated in this study. The Spearman test was employed to examine the non-probability sampling methods used in this investigation. The research results showed that there is a relationship between nutritional status and nutrient intake, and that nutrient intake and nutritional status are related, and then learning should be focused, so it is better for students to consume a variety of foods to improve the students' nutritional status and concentration.